Impact of Si on C, N, and P stoichiometric homeostasis favors nutrition and stem dry mass accumulation in sugarcane cultivated in tropical soils with different water regimes - Costa, Milton Garcia [UNESP]; Sarah, Marcilene Machado dos Santos [UNESP]; Prado, Renato de Mello [UNESP]; Palaretti, Luiz Fabiano [UNESP]; Piccolo, Marisa de Cássia; Souza Júnior, Jonas Pereira de [UNESP] (Frontiers, 2022)
Studies with silicon (Si) in sugarcane indicate a greater response in productivity in plants under stress, and the underlying mechanisms of Si in the crop are poorly reported. In this context, the benefits of Si in the crop’s stem production are expected to occur at the C:N:P stoichiometry level in plant tissues, benefiting plants with and without stress. However, the extension of this response may vary in different soils. Thus, this research aimed to evaluate if fertigation with Si modifies the C:N:P stoichiometry and if it can increase sugarcane’s nutritional efficiency and vegetative and productive parameters. Therefore, three experiments were installed using pre-sprouted seedlings to cultivate sugarcane in tropical soils belonging to the Quartzarenic Neosol, Eutrophic Red Latosol, and Dystrophic Red Latosol classes. The treatments comprised a 2 × 2 factorial scheme in each soil. The first factor was composed without water restriction (water retention = 70%; AWD) and with water restriction (water retention = 35%; PWD). The second factor presented Si concentrations (0 mM and 1.8 mM) arranged in randomized blocks with five replications. Fertigation with Si increases the Si and P concentration, the C and N efficiency, the C:N ratio, and the dry mass production. However, it decreases the C and N concentration and the C:P, C:Si, and N:P ratios in sugarcane leaves and stems regardless of the water regime adopted in the three tropical soils. Cluster and principal components analysis indicated that the intensity of the beneficial effects of Si fertigation on sugarcane plants varies depending on the cultivation soil and water conditions. We found that Si can be used in sugarcane with and without water stress. It changes the C:N:P homeostasis enough to improve the nutritional efficiency of C, P, N, and, consequently, the dry mass accumulation on the stems, with variation in the different cultivated soils.
Keywords: abiotic stress; beneficial element; fertigation with si; Saccharum officinarum L; water deficit